Cherishing men from afar Qing guest ritual and the Macartney Embassy of 1793 - Hevia, James Louis 1947- (Duke University Press, 1995)
Introduction -- A multitude of lords : the Qing Empire, Manchu rulership, and interdomainal relations -- Planning and organizing the British embassy -- King Solomon in all his glory : the British embassy in China -- Guest ritual and interdomainal relations -- Channeling along a centering path : greeting and preparation -- Convergence : audience, instruction, and bestowal -- Bringing affairs to a culmination -- Guest ritual and diplomacy -- From events to history : the Macartney embassy in the historiography of Sino-Western relations